The assembly of large BACs by in vivo recombination. - Mejía, J; Larin, Z (2000)
We have developed a method for recombining bacterial artificial chromosomes (BACs) and P1 artificial chromosomes (PACs) containing large genomic DNA fragments into a single vector using the Cre-lox recombination system from bacteriophage P1 in vivo. This overcomes the limitations of in vitro methods for generating large constructs based on restriction digestion, ligation, and transformation of DNA into Escherichia coli cells. We used the method to construct a human artificial chromosome vector of 404 kb encompassing long tracts of alpha satellite DNA, telomeric sequences, and the human hypoxanthine phosphoribosyltransferase gene. The specificity of Cre recombinase for loxP sites minimizes the possibility of intramolecular rearrangements, unlike previous techniques using general homologous recombination in E. coli, and makes our method compatible with the presence of large arrays of repeated sequences in cloned DNA. This methodology may also be applied to retrofitting PACs or BACs with markers and functional sequences.